(untitled) (Research, Society and Development, 2022)
Objectives: Evaluate the physical structure of a university restaurant according to the criteria for Good Manufacturing Practices, analyze the dimension of the sectors, the production flow and suggest a new layout. Methods: This is a study with descriptive design, carried out in a University Restaurant in Salvador, Bahia. The research was carried out in three stages: I - application of the checklist for the analysis of Good Manufacturing Practices; II - the physical dimensioning of the Unit was evaluated according to the literature, and the production flow through the floor plan; III - suggestion of new sizing and production flow. Results: The Unit obtained 65.03% (Group 2) of compliance with health legislation. The dimensioning of the Unit’s sectors presented a reduction of, on average, 42.13% in relation to what is recommended in the consulted literature. The new proposed layout made better use of the spaces and expanded the production area by 102.18m² even without exceeding the space already available by the Institution, in addition to solving the problem of flow crossings. Conclusion: The Unit presented several inadequacies in relation to legislation and the requirements of Good Manufacturing Practices and undersized physical sizing presentation. These factors contribute to the increased risk of cross-contamination that can favor the occurrence of foodborne illnesses.